A RATIONAL BUCKLING MODEL FOR THROUGH GIRDERS - Hasan Santoso (Institute of Research and Community Outreach - Petra Christian University, 2000)
Buckling of a through girder generally is predicted by the so called U-frame approach which treats the compressed top flanges as compression members restrained elastically by the web stiffness. This study used a line-type finite element analysis to examine buckling behaviour of through girders, both a single span girder and a continuous girder. The elastic buckling loads were plotted for a range of span to height ratio.